PASARAN NIAGA HADAPAN: SUATU TINJAUAN - Ahmad, Khairul Anuar (Jurnal Syariah, 2019)
This article attempts to review futures market in term of its application as well as to discuss it according to Islamic perspective. Having discussed it, it is observed that Islam is in tendency to prohibit this such transaction. However, a further research need to be conducted to examine it properly by utilised u~ul al-fiqh as well as considering current economic situation.